Devs Modeling and Simulation of the Loading and Hauling Process in Open Pit Mines - Moreno-Herrera, F (Institute of Electrical and Electronics Engineers Inc., 2023)
Chile is the world s leading copper producer, with more than 5.6 million tons produced in 2020. Most of the produced ore comes from open pit mines, whose extraction process consists of different subprocesses, with ore hauling incurring the highest operational cost. Tools to improve this subprocess are of paramount importance. Most tools use approaches that rely on optimization based on analytical methods. However, these fail to capture human behavior or to consider fine-grained details. To this end, we present a DEVS (Discrete-Event System Specification) simulation model. The formal definition of DEVS helps with the design and experimentation. DEVS modular interfaces allow users to extend the model easily to consider more entities, mine layouts, and dispatching policies. Simulations of the model delivered precise results compared to the literature, providing a valuable tool for decision-making in the mining industry. © 2023 IEEE.